Applying sustainability principles in the economy - Grundey, Dainora (Technological and Economic Development of Economy, 2008)
Editorial“Applying sustainability principles in the economy” Technological and Economic Development of Economy, 14(2), 101–106. Guest Editor Prof. Dainora GrundeyFirst published online: 21 oct 2010